ASPEK HUKUM PENGADAAN BARANG DAN JASA PEMERINTAH, SUATU TINJAUAN YURIDIS PERATURAN PENGADAAN BARANG DAN JASA PEMERINTAH - Musa Darwin Pane (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2017)
Procurement of goods and services for the benefit of the government is one tool to drive the wheels of the economy, in order to improve the national economy to the welfare of Indonesian life, for the procurement of goods and services, especially in the public sector is closely linked to the use of the state budget. Through normative juridical research, this study found the legal aspects of government procurement of goods and services, especially in terms of a review of the juridical rules of government procurement. Arrangements regarding the procedures for the procurement of government goods and services in Presidential Decree No. 54 Year 2010 jouncto Presidential Decree No. 70 The year 2012 is expected to increase conducive investment climate, efficiency of public spending, and accelerating the implementation of APBN/APBD. Government procurement of goods and services currently on aspects of administrative law, civil law and criminal law. In the procurement of goods and services should apply the general principles, good principles that have long been known in state financial management, such as the principle annual, the principle of universality, the principle of unity, and the principle of specialty as well as the principles of the new as reflecting best practices (application of the rules good) in the management of state finances.